Transient characteristics of internal flow fields of mixed-flow pump with different tip clearances under stall condition. (June 2021) - Ji, Leilei; Li, Wei; Shi, Weidong; Agarwal, Ramesh
This paper investigates the influence of different tip clearances on the transient characteristics of mixed-flow pump under stall condition. The instantaneous internal flow fields of mixed-flow pump with four tip clearances (0.2 mm, 0.5 mm, 0.8 mm and 1.1 mm) are explored by conducting unsteady time accurate simulations. Reynolds-averaged Navier-Stokes (RANS) equations are employed in the simulations and the results of computations are compared with experimental data. The results show that the pump head decreases by 22.1% and the pump efficiency drops by 13.9% at design flow condition when the impeller tip clearance increases from 0.2 mm to 1.1 mm. The swirling flow occurs in the inlet pipe of the mixed-flow pump with different tip clearances under stall condition, and the initial starting point of the swirling flow gets further away from the impeller inlet with increase in tip clearance because of increase in circumferential velocity and change in momentum of the tip leakage flow (TLF). The high turbulent eddy dissipation (TED) regions in the flow are attributed to the TLF, swirling flow, back flow and stall vortex, and their intensity are affected by the change in tip clearance. The oscillating trend of time domain distribution of TED enhances first and then decreases with increase in tip clearance and it exhibits a propagation feature under the effect of stall vortex, while most of the energy in the frequency domain remains concentrated in the low frequency part under stall condition.